Pervaporation of acetic acid/water mixture through polyphenylsulfone (ppsu) membrane modified with sodium alginate/polyaniline - Nur Ulya Binti Razali (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The pervaporation process is a developed technique in separation technology. Although the development is still new, pervaporation is one of the membrane separation process that has attracted interest in the chemicals industries. Pervaporation process is a simple process and easy to operate when compared with other conventional separation process such as distillation. This study focus on the potential of pervaporation process applied to separate the acetic acid solutions from water mixture. The polyphenylsulfone (PPSU) membrane were used. Three types of synthesized membrane were prepared via phase inversion-immersion precipitation method with composition of 25 wt%, 27.5 wt% and 30 wt% PPSU. The pervaporation study was conducted using different concentration of acetic acid as a feed solution. The degree of swelling for each membrane was calculated by using different acetic acid concentration (0, 80, 90 and 100 wt%). It showed that 25 wt% PPSU membrane was the lowest degree of swelling while 30 wt% PPSU was the highest total degree of swelling. It was found that the flux at the 25 wt% PPSU membrane was the highest and for 27.5 wt% PPSU membranes was the lowest. Therefore, 27.5 wt% PPSU membrane was selected to further modified by in situ chemical oxidative polymerisation method to form a composite membrane of sodium alginate/polyaniline. The membranes were characterized by using Scanning Electron Microscopy (SEM) in order to study the morphology while membrane functional groups have been using Fourier Transform Infrared Spectorcopy (FTIR) and the surface membrane roughness was observed via Atomic Force Microscopy (AFM).